Application of virtual reality head mounted display for investigation of movement: a novel effect of orientation of attention. (12th August 2016) - Quinlivan, Brendan; Butler, John S; Beiser, Ines; Williams, Laura; McGovern, Eavan; O'Riordan, Sean; Hutchinson, Michael; Reilly, Richard B
Abstract: Objective. To date human kinematics research has relied on video processing, motion capture and magnetic search coil data acquisition techniques. However, the use of head mounted display virtual reality systems, as a novel research tool, could facilitate novel studies into human movement and movement disorders. These systems have the unique ability of presenting immersive 3D stimulus while also allowing participants to make ecologically valid movement-based responses. Approach. We employed one such system (Oculus Rift DK2) in this study to present visual stimulus and acquire head-turn data from a cohort of 40 healthy adults. Participants were asked to complete head movements towards eccentrically located visual targets following valid and invalid cues. Such tasks are commonly employed for investigating the effects orientation of attention and are known as Posner cueing paradigms. Electrooculography was also recorded for a subset of 18 participants. Main results. A delay was observed in onset of head movement and saccade onset during invalid trials, both at the group and single participant level. We found that participants initiated head turns 57.4 ms earlier during valid trials. A strong relationship between saccade onset and head movement onset was also observed during valid trials. Significance. This work represents the first time that the Posner cueing effect has been observed in onset of head movement in humans. The results presented here highlight the role of head-mounted display systems as a novel and practical research tool for investigations of normal and abnormal movement patterns.